2007
DOI: 10.3122/jabfm.2007.06.060067
|View full text |Cite
|
Sign up to set email alerts
|

Health Problems Presented to Family Practices in The Netherlands 1 Year Before and 1 Year After a Disaster

Abstract: Background: Disasters often have negative health consequences. Studies of health problems presented in family practice before and after a disaster are rare. The present study analyzed health problems before and after a disaster and predictors of increased morbidity after the disaster as presented in family practice.Methods: A matched cohort study design with measurements 1 year before the disaster and 1 year after the disaster. Victims (N ‫؍‬ 9183) and matched controls (N ‫؍‬ 7066) were surveyed in the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Risk factors for MHSU after disaster include (a) level of exposure to disasterbeing trapped even if uninjured, residence in an affected area (Boscarino, Adams, Stuber, & Galea, 2005;Dorn et al, 2006;Smith, Christiansen, Vincent, & Hann, 1999;; (b) indirect consequences of disaster -loss of a child or relocation (Dorn et al, 2006;Soeteman et al, 2007;van der Velden, Yzermans, Kleber, & Gersons, 2007b); (c) residence in a geographically proximate area (Ford, Adams, & Dailey, 2006); (d) having a perievent panic attack (Boscarino, Adams, Stuber, et al, 2005); (e) access -having private insurance, a regular doctor (Boscarino, Adams, Stuber, et al, 2005;van der Velden et al, 2007b); (f) demographics -female gender, single, migrant status, white race (Boscarino, Adams, Stuber, et al, 2005;van der Velden et al, 2007b); (g) history of psychological problems (Soeteman et al, 2007;van der Velden et al, 2007b); (h) poor post-disaster mental health or mental health symptomatology (Ford et al, 2006;Jordan et al, 2004;van der Velden et al, , 2007b; and (i) receiving post-disaster mental health treatment (den Ouden et al, 2005;van der Velden et al, 2007b).…”
Section: Health Systems and Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for MHSU after disaster include (a) level of exposure to disasterbeing trapped even if uninjured, residence in an affected area (Boscarino, Adams, Stuber, & Galea, 2005;Dorn et al, 2006;Smith, Christiansen, Vincent, & Hann, 1999;; (b) indirect consequences of disaster -loss of a child or relocation (Dorn et al, 2006;Soeteman et al, 2007;van der Velden, Yzermans, Kleber, & Gersons, 2007b); (c) residence in a geographically proximate area (Ford, Adams, & Dailey, 2006); (d) having a perievent panic attack (Boscarino, Adams, Stuber, et al, 2005); (e) access -having private insurance, a regular doctor (Boscarino, Adams, Stuber, et al, 2005;van der Velden et al, 2007b); (f) demographics -female gender, single, migrant status, white race (Boscarino, Adams, Stuber, et al, 2005;van der Velden et al, 2007b); (g) history of psychological problems (Soeteman et al, 2007;van der Velden et al, 2007b); (h) poor post-disaster mental health or mental health symptomatology (Ford et al, 2006;Jordan et al, 2004;van der Velden et al, , 2007b; and (i) receiving post-disaster mental health treatment (den Ouden et al, 2005;van der Velden et al, 2007b).…”
Section: Health Systems and Infrastructurementioning
confidence: 99%
“…Risk factors for non-specific mental health problems include (a) direct exposure level to disaster -degree of exposure (de Mel, McKenzie, & Woodruff, 2008;Norris et al, 2002;Wang et al, 2000), witnessing injury, death, or destruction (Ghaffari-Nejad, Ahmadi-Mousavi, Gandomkar, & Reihani-Kermani, 2007;Thomas, 2006), and direct threat of disaster (Thomas, 2006); (b) participation in rescue and cleanup (Dirkzwager et al, 2004;Huizink et al, 2006;Slottje et al, 2007;Spinhoven & Verschuur, 2006); (c) media exposure (Ford, Adams, & Dailey, 2007;Thomas, 2006;Wayment, 2004); (d) characteristics of the disaster -mass violence/intentional man-made event rather than an accidental or a natural disaster (Norris et al, 2002;Thomas, 2006); (e) indirect consequences of disaster -having a child with a severe injury (Dorn, Yzermans, Spreeuwenberg, & van der Zee, 2007), having a close one affected by disaster (Slottje et al, 2007), relocation or residential problem (Dirkzwager et al, 2006;Foster, 2002;Ghaffari-Nejad et al, 2007;Soeteman et al, 2007;Thomas, 2006), or community destruction (Thomas, 2006); (f) proximityproximity to disaster (Foster, 2002;Thomas, 2006), being in the disaster-affected area/city at the time of disaster (Ghaffari-Nejad et al, 2007;Remennick, 2002;Smith et al, 1999;Soeteman et al, 2007), working near the disaster site (Trout et al, 2002); interestingly, some research has found signs of distress in geographically distant groups immediately after disaster, but with no change in ongoing moods (Whalen, Henker, King, Jamner, & Levine, 2004); (g) alcohol problems since disaster -alcohol depen...…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In Volendam en in Enschede werd een tijdelijke verhoging gevonden van het voorkomen van lichamelijk onverklaarde klachten (vooral van het bewegingsapparaat en het spijsverteringskanaal) die na enige maanden terugkeerde naar het niveau van de referentiegroep en/of de periode voor de ramp (Soeteman et al, 2006). In de eerste maanden ging het hierbij vooral om slaapproblemen, stressreacties en een angstig, nerveus gevoel, terwijl na ongeveer drie jaren de nadruk lag op moeheid, malaise en een depressieve stoornis.…”
Section: Resultatenunclassified
“…We have 2 papers from The Netherlands, a country with a strong tradition of primary care research. Soeteman et al 7 consider the types of health problems that increase after a disaster, and the predictors thereof, as found in family medicine offices providing continuity of care before and after the disaster. This may have increased importance in an age of terrorism.…”
mentioning
confidence: 99%